Deontic logic in computer science 11th International Conference, DEON 2012, Bergen, Norway, July 16-18, 2012. Proceedings - Broersen, Jan; Elgesem, Dag (Lecture Notes in Computer Science, 2012)
This volume presents the refereed proceedings of the 11th International Conference on Deontic Logic in Computer Science, DEON 2012, held in Bergen, Norway, in July 2012. The 14 revised papers included in the volume were carefully reviewed and selected from 29 submissions. Topics covered include logical study of normative reasoning, formal analysis of normative concepts and normative systems, formal specification of aspects of norm-governed multi-agent systems and autonomous agents, normative aspects of protocols for communication, negotiation and multi-agent decision making, formal representation of legal knowledge, formal specification of normative systems for the management of bureaucratic processes in public or private administration, and applications of normative logic to the specification of database integrity constraints.